Utilization of QR - Code in Citizenship Education - Subarjo, Abdul Haris (Institut Teknologi Dirgantara Adisutjipto, 2018)
Challenges in the era of the 21st century and revolution 4.0 must be answered by all parties. Likewise with the education sector, besides providing knowledge, it also has an obligation to equip the younger generation with national identity and identity as well as awareness of roles in the future. This ability is obtained through learning / courses. The citizenship (Kewarganegaran) course also carries out this task so that it needs to be made an innovation in lectures using a QR Code-based media on Human Rights material. The making of media uses a development research model that refers to Thiagarajan's 4D RnD research design. The results of this study are 1)composed of a learning media on the sub-topic of Human Rights., 2) QR code can be used as an innovation in the preparation of learning media in citizenship courses. 3) Through the use of QR code smartphones can be used as a medium for mobile-learning.